Parathyroid immunohistochemistry in a 12‐year‐old mixed‐breed dog with parathyroid adenocarcinoma. Issue 3 (9th July 2018) - Kaiser, Anna‐Maria; Kempker, Lena; Neiger, Reto
Abstract : Summary: A 12‐year‐old, female, spayed, mixed‐breed dog with acute lethargy, anorexia and weakness and markedly elevated total and ionised calcium concentration showed an enlarged left cranial parathyroid gland on ultrasonography of the ventral neck. Despite preoperative therapy with furosemide and calcitonin, there was no decline of plasma ionised calcium concentration. The dog deteriorated rapidly and was euthanased two days after initial presentation. Postmortem histopathology revealed parathyroid tissue with characteristics of malignancy as local and vascular invasion. Immunohistochemistry showed parathyroid hormone positive staining of these cells. Unusual clinical presentation and histopathological characteristics are discussed.